Ikhlas = Prososial ? (Studi Komparasi Berdasar Caps) - Chizanah, Lu’luatul (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2011)
Ikhlas is often interpreted as sincerity in helping or prosocial. This study aimed to test the common assumption by performing a comparative study based on the components in CAPS as the parameters. It results that in general, ikhlas and prosocial have some similarities: (1) involves both affective and cognitive systems, (2) carrying the idealism of discourse, and (3) leads to the normative construct. However, substantively, ikhlas and prosocial are two constructs that are different.Â